Analisis Profitabilitas dan Likuiditas pada PT Pertamina Geothermal Energy Tbk. - Erawati, Teguh; Listyawati, Reni; Adelvia , Adelvia; Vika Maharani, Erliana; Bule, Ratnawati; Novantri Wae, Florentina (SMARTINDO, 2024)
This research aims to analyze the level of profitability and liquidity of PT Pertamina Geothermal Energy Tbk. as one of the geothermal energy companies listed on the Indonesia Stock Exchange in the 2021-2023 period. The research uses a quantitative descriptive approach by utilizing secondary data in the form of company financial reports. The financial ratios analyzed include Current Ratio, Quick Ratio, Cash Ratio, Net Profit Margin (NPM), Return On Equity (ROE), and Return On Assets (ROA). The results of the analysis show an increase in the company's financial performance, especially in 2023, where the Current Ratio reached 353.65%, indicating very good liquidity, as well as an NPM of 40.26%, which reflects the company's operational efficiency in generating profits. This research contributes to stakeholders, such as management and investors, in understanding the company's financial condition and making strategic decisions for future business sustainability.